For Geographies of Children, Young People and Popular Culture. Issue 10 (October 2014) - Horton, John
Abstract This paper calls for more direct, careful, sustained research on geographies of children, young people and popular culture. I present three sets of empirical and conceptual resources for researchers developing work in this area. Part 1 signposts classic work from cultural/media studies, marketing and sociology, which has been centrally concerned with meanings of popular culture designed for children and young people (e.g. via critiques of the gendered content of iconic popular cultural phenomena). Part 2 foregrounds nascent conceptualisations of social‐material geographies of childhood and youth. I argue that these conceptualisations can extend and unsettle classic work on popular culture, by questioning how popular cultural texts, objects and phenomena matter. Halfway through the paper is a 'commercial break'. Here, I present some personal reflections on working at the intersection between the ideas discussed in Parts 1 and 2. With reference to a specific popular cultural artefact (the Toys 'Я' Us Christmas toy catalogue), I argue that both meanings and matterings are crucial for geographers engaging with children and young people's popular cultures. In conclusion, I argue that more geographers should engage with the literature and issues outlined in Part 1, but also that the geographical concepts discussed in Part 2 demand new modes of research, thinking and writing in relation to popular cultural texts, objects and phenomena.